Images and voices that perpetuate school failure in children from lower social classes (Olhar de Professor, 2011)
An image, a charge or any other image, can be used to denounce the process of exclusion and selection that occurs in Brazilian schools. This article emphasizes the need to intensify the discussion about the messages conveyed in charges as images form opinions and concepts, in particular in lower social classes. The article intends to show that the interpretation of an image enlivens our beliefs, values and conventions that come from the personal and social imaginary, where the intertextual possibility and image polyphony perpetuates school failure in children from lower social classes.
Keywords: Charge. School failure. Imaginary.